2001
DOI: 10.1093/hmg/10.22.2493
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear localization of mRNA and protein products of COCH, mutated in the sensorineural deafness and vestibular disorder, DFNA9

Abstract: Missense mutations in the COCH gene, which is expressed preferentially at high levels in the inner ear, cause the autosomal dominant sensorineural deafness and vestibular disorder, DFNA9 (OMIM 601369). By in situ hybridization of mouse and human inner ear sections, we find high-level expression of COCH mRNA in the fibrocytes of the spiral limbus and of the spiral ligament in the cochlea, and in the fibrocytes of the connective tissue stroma underlying the sensory epithelium of the crista ampullaris of the semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 33 publications
4
77
2
Order By: Relevance
“…2A, lane 1). This is consistent with the expected major cochlin polypeptides previously reported in bovine inner ear extracts (Ikezono et al 2001) and the 60 and 40 kDa bands reported in fetal human inner ear extract (Robertson et al 2001). The specificity of the antibody was confirmed by peptide inhibition, and no primary antibody controls ( Fig.…”
Section: Antibodies To Ivd2 Identify Cochlin Polypeptides In Inner Easupporting
confidence: 91%
“…2A, lane 1). This is consistent with the expected major cochlin polypeptides previously reported in bovine inner ear extracts (Ikezono et al 2001) and the 60 and 40 kDa bands reported in fetal human inner ear extract (Robertson et al 2001). The specificity of the antibody was confirmed by peptide inhibition, and no primary antibody controls ( Fig.…”
Section: Antibodies To Ivd2 Identify Cochlin Polypeptides In Inner Easupporting
confidence: 91%
“…The deposits were found at exactly the same places in temporal bone sections. 8 It was therefore suggested that mutant protein may have a direct or indirect effect on these fibrocytes and lead to degeneration. This may have a negative impact on the inner ear, possibly by interfering with K þ recycling, which is thought to play an important role in ion homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…COCH mRNA is known to be predominantly expressed in the inner ear 7,8 and recent proteomic analysis indicated that the COCH protein, cochlin, constitutes 70% of all inner ear proteins, 9 suggesting that this protein plays an important role in the inner ear. The human COCH gene contains two different types of domains, a region homologous to a domain in factor C of Limulus (FCH, factor C homologous domain; sometimes also referred to as LCCL domain) 10 and two von Willebrand factor A-like domains (vWFA1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of primary TM cells in vitro in response to the presence of exogenous cochlin suggests that this may be mediated by extracellular protein-protein interactions. Three cochlin isoforms (~40, ~46 and ~60 kDa) have been described in the human cochlea (Robertson et al, 2001), indicating molecular heterogeneity within the inner ear in vivo. It was initially postulated that size heterogeneity of cochlin may be due to alternative mRNA splicing, exon skipping or posttranslational modifications (Robertson et al, 1997).…”
Section: Cochlin and Extracellular Matrixmentioning
confidence: 99%